The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1023/a:1008437805286
|View full text |Cite
|
Sign up to set email alerts
|

A randomised, concentration-controlled, comparison of standard (5-day) vs. prolonged (15-day) infusions of etoposide phosphate in small-cell lung cancer

Abstract: A randomised, concentration-controlled, comparison of standard (5-day) vs. prolonged (15-day) infusions of etoposide phosphate in small-cell lung cancer

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Etoposide is a cell‐cycle specific cytotoxic drug: the cells have to be exposed to it during the sensitive part of the cell cycle (late S‐phase) and exposure maintained for long enough to kill the cells. The therapeutic window is highly dependent on the duration of the infusion [9]. Duration above a certain threshold concentration was therefore found to be the best predictor of efficacy in small‐cell lung cancer.…”
Section: Systemic Exposure Indicesmentioning
confidence: 99%
“…Etoposide is a cell‐cycle specific cytotoxic drug: the cells have to be exposed to it during the sensitive part of the cell cycle (late S‐phase) and exposure maintained for long enough to kill the cells. The therapeutic window is highly dependent on the duration of the infusion [9]. Duration above a certain threshold concentration was therefore found to be the best predictor of efficacy in small‐cell lung cancer.…”
Section: Systemic Exposure Indicesmentioning
confidence: 99%
“…For etoposide, a topoisomerase II inhibitor, haematological toxicity is closely related to unbound drug exposure [10,11]. Joel et al [12] hypothesized the existence of a therapeutic window, but further studies are needed to better de®ne the therapeutic concentration or exposure to etoposide.…”
Section: Introductionmentioning
confidence: 99%
“…Etoposide phosphate infusions allow prolonged scheduling of etoposide with pharmacokinetic monitoring to allow dose adjustments. Trials in our unit over the past decade have shown this to be feasible and well tolerated (O'Byrne et al, 1997;Joel et al, 1998;Braybrooke et al, 2003). Experience from previous studies, together with the preclinical data presented here, led to the adoption of the sequential administration of topotecan for 5 days followed by EP for 5 days as a novel regimen to be investigated in this phase I study in patients with advanced ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…On the morning of day 7 (18 h after the start of the infusion) and on day 9 of each cycle, peripheral venous blood samples were drawn for determination of total plasma etoposide levels, as described previously (Harvey et al, 1985a;Joel et al, 1996Joel et al, , 1998. Plasma standards covering the range 0.5 -5.0 mg ml À1 were used; patient samples were run in duplicate, with quality control samples at two concentrations (1.25 and 3.5 mg ml À1 ).…”
Section: Therapeutic Drug Monitoringmentioning
confidence: 99%
See 1 more Smart Citation